Factors affecting implementation of the nursing process among nurses at Nchanga north general hospital in Chingola district Zambia - Phiri Reagan (Lusaka, the university of Zambia, school of medicine, 2016)
This study was conducted at Nchanga general hospital in Chingola district to determine the factors affecting the implementation of the nursing process among nurses. The nursing process is a systematic problem solving approach of giving individualized nursing care.
Dissertation submitted in partial fulfilment forn the award of bachelors degree in nursing scieces at the university of Zambia.
Includes bibliographic references.
Keywords: Nursing process